From nature trails to nature experience trails – a historical overview of the evolution of nature trails (Training and Practice : Journal of Educational Sciences, 2020)
The study presents the history of the creation of nature trails (educational paths) from the beginning to the appearance of nature experience trails with an international focus, with a special focus on German-speaking areas. The evolution of nature trails can be examined on the basis of available literature primarily in the United States, Germany, Austria, Switzerland and the United Kingdom. In Hungary, the educational paths and nature experience trails appeared later than in the above mentioned countries. According to our research results, we may demonstrate that among early international nature trails there were a few that focused on educational aspects, too. Unfortunately, in Europe this tendency has not become the part of planning either in the case of international or in Hungarian nature trails.